Genome Mapping and Genomics in Laboratory Animals - Denny, Paul.; Denny, Paul.; Kole, Chittaranjan.; Kole, Chittaranjan. (Genome Mapping and Genomics in Animals,, 2012)
Mapping of animal genomes has generated huge databases and several new concepts and strategies, which are useful to elucidate origin, evolution and phylogeny. Genetic and physical maps of genomes further provide precise details on chromosomal location, function, expression and regulation of academically and economically important genes. The series Genome Mapping and Genomics in Animals provides comprehensive and up-to-date reviews on genomic research on a large variety of selected animal systems, contributed by leading scientists from around the world. Laboratory animals are those species that by accident of evolution, domestication and selective breeding are amenable to maintenance and study in a laboratory environment. Many of these species are studied as 'models' for the biology and pathology of humans. Laboratory animals included in this volume are sea-urchin, nematode worm, fruit fly, sea squirts, puffer fishes, medaka fish, African clawed frog, mouse and rat.